Conflict in Nepal - Sapkota, Khila (Economic Journal of Nepal, 2005)
Society contains a lot of social interactions regarding its structure and functions. Such interactions are so indifferent and inseparable from the entire range of social relationship that those are regarded as a natural and compulsory process of social behavior. The main processes of social interaction are cooperation, competition, conflict, accommodation, assimilation, and integration. The theme of this paper is only the basis of conflict. When we cast our glance at the social life it seems clearly that not only cooperation but also conflict is an essential and natural aspects of human life. In the context of politics conflict is very violent. Even when we see to other spheres apart from political sphere we can find conflict in the family between husband and wife, between brothers, between neighbors, between students, between two parties, between farmers, between government and antigovernment and so on; but it is also a bitter truth that hundred percent cooperation, love and sacrifice is impossible in any family because sometimes there is also an occurrence of dispute, conflict and misunderstanding. This very bitter truth is applicable to the society also. Economic Journal of Nepal Vol.28(4) 2005 pp.257-263